PERANCANGAN ALAT DAN SISTEM PEMANTAUAN PENDAKI GUNUNG BERBASIS INTERNET OF THINGS (IOT) - Indra Gunawan; Muhamad Sadali; Suhartini Suhartini; Imam Fathurrahman (Politeknik Bisnis Indonesia, 2022)
Climbing generally refers to a long journey and usually takes a small path leading to a higher place such as the top of a mountain. When climbing, sometimes novice climbers do not know the basics of climbing, resulting in unwanted events such as the wrong way, so there needs to be a system for monitoring the position of climbers from the guard post. This system, helps managers to monitor the whereabouts of climbers from the start to the location that climbers want to visit where the position data is processed by the Lora Module and displayed on the OLED and the application website as a monitoring system. This tool is in the form of a Radio Frequency Identification (RFID) bracelet and (RFID) Reader to detect climbers, every climber who registers to climb will be given a Radio Frequency Identification (RFID) bracelet. on the tools that have been provided, so that the manager knows the climbers are already at the post through the monitoring website. The results of this study are in the form of a tool product in the form of a bracelet which is scanned in an RFID Reader then the data will be sent via a wireless network to a web server/web application on the coast guard post, the test results obtained that the tool can be read properly and the process of sending data to the web application takes about 2 seconds.